Streamflow sensitivity regimes of alpine catchments: seasonal relationships with elevation, temperature, and glacier cover - M Weiler; S Gnann; K Stahl (Environmental Research Letters, 2025)
Alpine streams supply water to mountains and downstream regions, but their sensitivity to climatic variability is complex. Here, we derive streamflow sensitivity regimes from long-term observations in the Swiss Alps and analyse their potential controls. For each week of the year, we estimated absolute and relative sensitivities of streamflow in response to changes in temperature, precipitation, and storage. At high elevations with extensive glacier cover, weekly temperature and precipitation sensitivities peak in spring and summer when melt rates are high. At low elevations with no glacier cover, weekly temperature sensitivities are negative in summer, while precipitation sensitivities are highest under moist winter conditions. The elevation at which temperature sensitivities switch from positive to negative changes over the course of the year, showing that the sensitivities are temperature-dependent and thus non-stationary. Weekly streamflow sensitivities help resolve the seasonally-varying drivers of the streamflow regime and may be used to evaluate hydrological models.